Pengaruh Lifestyle, Cafe Atmosphere, Customer Experience, Price Dan Service Quality Terhadap Revisit Intention Gen Z Di Kopi Kampus Jember - Ilma Hidayatur Rofida (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine and analyze the partial and simultaneous influence of lifestyle, café atmosphere, customer experience, price and service quality variables on Gen Z revisit intention at Kopi Kampus Jember. The background of this research is based on the phenomenon of increasing cafe business competition in Jember City and the consumptive behavior of Gen Z which dominates the cafe visitor segment. Kopi Kampus Jember recorded a rating of 4.3 from 435 reviews on Google Maps, but several reviews indicated consumer dissatisfaction with service quality which could affect revisit intention. The type of research used is quantitative with an associative approach. The research population includes all consumers of Kopi Kampus Jember with a total sample of 60 respondents using purposive sampling technique. Data analysis methods used include descriptive statistics, instrument tests (validity and reliability), classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing (t-test and F-test). The results showed that the lifestyle variable has no significant effect on revisit intention (t-count 0.687 < t-table 2.004; sig. 0.495 > 0.05). The café atmosphere, customer experience, and price variables have a positive and significant effect on revisit intention. Meanwhile, the service quality variable has a negative and significant effect on Gen Z revisit intention at Kopi Kampus Jember (t-count -4.103; sig. 0.000). Simultaneously, all independent variables have a positive and significant effect on revisit intention (F-count 34.954 > F-table 2.382; sig. 0.000). The coefficient of determination (Adjusted R²) of 0.742 indicates that the five variables are able to explain 74.2% of the variation in revisit intention.